The Role of United Nation in Addressing Human Rights Violations on Syria’s Internal Conflicts - Kasanusi, Kasanusi; Solikhah, Mar'atus; Triristina, Nensy; Pujiyanti, Yunita Rizki; Khoiruddin, Khoiruddin (International Journal Labs, 2022)
Background: Syria is one of many Arab countries in the Middle East that are undergoing revolution and civil war. It was motivated by the authoritarian attitude of the government and the economic downturn that occurred until there was popular resistance to Bashar al-Assad's regime. This conflict in Syria has attracted worldwide attention, because one of these cases in Syria has entered into the most glaring case today, namely regarding human rights violations. Aim: This paper is intended to discuss the role of the United Nations (UN) in human rights violations in the Syrian conflict, the conflict in Syria the ruling government that uses the tools of the state (military) to deal with protests by its people, thus, triggers a domestic battle between the government (the ruling regime of Bashar al-Assad) and the civilians. Method: This paper uses qualitative research techniques with role theory analysis, with a realist theory approach, namely by describing the roles of international organizations (United Nations) where through secondary data, produce descriptive data according to analysis and existing facts of the subject or object observed. Findings: Efforts by the UN and the international community to uphold human rights in Syria are to send former UN secretary-general Kofi Annan to trade in Syria, as well as the Arab League, which calls for opposition groups to unite and proposes the establishment of a transitional government on the proposal of the UN.